Detection of a protein phosphatase 2A holoenzyme in Neurospora crassa. - Einat Yatzkan; Viktor Dombradi; Oded Yarden (Fungal Genetics Reports, 1999)
A high molecular mass (about 280 kDa) protein phosphatase 2A holoenzyme was detected in a crude N. crassa extract by gel filtration coupled with phosphatase activity assays. According to Western blot analysis the holoenzyme consists of a 36-kDa catalytic subunit complexed with an additional, yet unidentified, regulatory subunit(s).